2017
DOI: 10.1111/bjh.14549
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib, lenalidomide, and dexamethasone in patients with relapsed multiple myeloma categorised by age: secondary analysis from the phase 3 ASPIRE study

Abstract: SummaryA primary analysis of the ASPIRE study found that the addition of carfilzomib to lenalidomide and dexamethasone (carfilzomib group) significantly improved progression‐free survival (PFS) compared with lenalidomide and dexamethasone alone (control group) in patients with relapsed multiple myeloma (RMM). This post hoc analysis examined outcomes from ASPIRE in patients categorised by age. In the carfilzomib group, 103/396 patients were ≥70 years old, and in the control group, 115/396 patients were ≥70 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 30 publications
(39 reference statements)
1
29
0
Order By: Relevance
“…The ASPIRE study of carfilzomib, lenalidomide, and dexamethasone (KRd) versus Rd demonstrated prolonged PFS with KRd in patients with relapsed multiple myeloma aged ≥ 70 years (median: 23.8 vs 16.0 months; HR, 0.75, 95% CI, 0.53-1.08) and an improved ORR (90.3% vs 66.1%, respectively). 24 While cardiovascular events occurred more frequently in the elderly population compared with patients aged <70 years, KRd demonstrated a favorable benefit-risk profile in elderly patients. 25 The ENDEAVOR study of carfilzomib and dexamethasone (Kd) versus Vd demonstrated prolonged PFS with Kd in patients with RRMM who received one to three prior lines of therapy and were aged 65 to 74 years (median: 15.6 vs 9.5 months; HR, 0.528, 95% CI, 0.382-0.728) or ≥ 75 years (median: 18.7 vs 8.9 months; HR, 0.383, 95% CI, 0.227-0.647).…”
Section: Discussionmentioning
confidence: 99%
“…The ASPIRE study of carfilzomib, lenalidomide, and dexamethasone (KRd) versus Rd demonstrated prolonged PFS with KRd in patients with relapsed multiple myeloma aged ≥ 70 years (median: 23.8 vs 16.0 months; HR, 0.75, 95% CI, 0.53-1.08) and an improved ORR (90.3% vs 66.1%, respectively). 24 While cardiovascular events occurred more frequently in the elderly population compared with patients aged <70 years, KRd demonstrated a favorable benefit-risk profile in elderly patients. 25 The ENDEAVOR study of carfilzomib and dexamethasone (Kd) versus Vd demonstrated prolonged PFS with Kd in patients with RRMM who received one to three prior lines of therapy and were aged 65 to 74 years (median: 15.6 vs 9.5 months; HR, 0.528, 95% CI, 0.382-0.728) or ≥ 75 years (median: 18.7 vs 8.9 months; HR, 0.383, 95% CI, 0.227-0.647).…”
Section: Discussionmentioning
confidence: 99%
“…For KRd, the incidence of grade $3 cardiac failure was higher in patients aged .70 years vs ,70 years (8.7% vs 2.1%). 16 For Kd, grade $3 cardiac failure occurred more frequently in patients $75 years of age compared with patients 65 to 74 years of age (10.4% vs 4.9%) or those ,65 years of age (10.4% vs 2.7%). 17 Because carfilzomib is approved and commonly used for RRMM, a clear understanding of its CV safety and benefit-risk profile is important.…”
Section: Introductionmentioning
confidence: 89%
“…Elderly patients with MM are a challenging population to treat, in part due to higher chemotherapy toxicities 30 and comorbidity burden 31,32 . In ENDEAVOR and ASPIRE, analyses of twice-weekly carfilzomib-based therapies by age demonstrated consistent improvements in PFS and OS compared with the control treatment arms across all subgroups 20,21 . In A.R.R.O.W., once-weekly Kd70 mg/m 2 improved PFS and ORR for all age subgroups versus twice-weekly Kd27 mg/m 2 .…”
Section: Discussionmentioning
confidence: 90%
“…Efficacy and safety of twice-weekly carfilzomib-based therapies were previously demonstrated in the phase 3 ASPIRE and ENDEAVOR trials [16][17][18][19] . Importantly, the treatment effect of carfilzomib was confirmed across several patient subgroups [20][21][22][23][24][25][26] . The favorable benefit-risk profile of twiceweekly carfilzomib-based therapies versus standards of care (SOCs) provided an opportunity to consider the value of more convenient once-weekly carfilzomib therapy for patients with RRMM.…”
Section: Introductionmentioning
confidence: 99%